Reformist Reforms, Non-Reformist Reforms, and Building a Youth-Centred Approach to Eviction Law and Practice - Buhler, Sarah (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
Eviction from rental housing is associated with an array of adverse consequences for people, with specific negative impacts on young people. Yet despite its harmful impacts, eviction is largely portrayed in Canadian residential tenancies law texts and processes as a routine consequence of a contractual breach, and eviction legal processes are managed in most Canadian jurisdictions by administrative tribunals that are designed to efficiently process landlord claims for possession. In short, existing laws and legal processes around eviction fail to reflect the realities of youth who struggle to find and retain adequate and affordable housing, let alone to engage in legal processes that are not designed with their lived experiences in mind. Our research sought to bring eviction laws and legal processes under scrutiny by young people with lived experience of the impacts of these laws and processes. Our central question was: what would it take to transform this part of the legal system to make it more responsive to young people’s lived realities and to advance their human right to housing? To do so, we held two workshops with young people in Saskatoon and Toronto in 2024. This paper discusses the ideas that were generated at the workshops, using Amna Akbar's framework of “reformist reforms” and “non-reformist reforms”. Participants suggested immediate changes ("reformist reforms") aimed at reducing harm and stabilizing housing. But they also generated more visionary ideas that urged the rejection of logics that position housing as a commodity, and that accept eviction as an inevitable feature of our current economic and legal systems. Their ideas urged a more radical reimagining of a world where eviction is not seen as normal but rather where communities and systems work to ensure that everyone has a safe and affordable place to call home.